Measurement of the ionization yield of neutron-induced proton recoils in Tetramethylsilane. (28th July 2021) - Wu, S.X.; Lenardo, B.G.; Gratta, G.
Abstract: We report on a low energy measurement of the ionization yield in a Tetramethylsilane Time Projection Chamber (TPC) using 2.8 MeV neutrons from a deuterium-deuterium neutron generator. The proton recoil charge yield is measured at four different electric fields, finding a dependence that can be described by the Thomas-Imel model. By comparing the proton recoil yield to that obtained from γ-ray calibrations, a quenching factor is obtained for each electric field. These results demonstrate the feasibility of using room temperature organic ionisation detectors to detect MeV-scale neutrons in the proton-recoil channel.